Sensitivity analysis of earthquake characteristics in relation to changes in path parameters - Sales, Nikka Marie B.; Azul, Kristian M. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The exposure of the Philippines to strong ground motions presses for a need of a better understanding of the said phenomenon. Historically, many prediction techniques are developed to simulate an earthquake depending on the nature of the location, the source and the path it traverses. In this study, the behavior of earthquake characteristics was analyzed by modelling synthetic earthquakes idealized in a solid rock formation where regional attenuation relationships (path parameters) were varied while the source and site condition properties were held constant. Basically, by varying the values of these regional attenuation relationships (the high frequency filter, geometrical spreading, anelastic attenuation, soil density, and shear wave velocity), the sensitivity of earthquake characteristics amplitude (Arias intensity, bracketed duration, predominant period, peak ground acceleration, and max amplitudes from the response spectra) from these variation, was analyzed. Results showed that there are significant changes on all the earthquake characteristics of interest when the selected path parameters are varied; except for the variation of the geometrical spreading which showed insignificant changes due to inappropriate between the idealized map and variation values. Also, the predominant period and the pseudo spectral velocity and displacement showed insignificant sensitivity with some path parameters. Lastly, an integral part of the analysis was observations in terms of hypocentral distance. Generally among most of the earthquake scenarios, the amplitude of earthquake characteristics decreases as the hypocentral distance increases.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Earthquake engineering -- Mathematical models; Earthquake simulators